Clinical pharmacogenetics of antiaggregants: clinical pharmacologist' point of view - D. A. Syche; A. V. Zyatenkov; B. G. Kukes (Российский кардиологический журнал, 2007)
The review is devoted to individual antiaggregant sensitivity issue. According to numerous studies' data, acetylsalicylic acid is ineffective in 5 % of the patients. It might be explained by target molecule (COG-1) gene polymorphism. This phenomenon has important clinical implications, as aspirin-resistant patients have significantly higher risk of thrombotic complications. Another widely used antiaggregant, clopidogrel, is ineffective in more than 15 % of the patients. Clopidogrel effectiveness depends on hepatic iso-enzyme CYP3A activity and ADP receptor gene variant. Many studies demonstrated that clopidogrel resistance worsens prognosis in coronary heart disease patients. Even new antiaggregants, Ilb-IIIa receptor inhibitors, are ineffective in 20 % of the cases, due to glycoprotein receptor gene polymorphism. Therefore, to identify optimal antiaggregant therapy regimen, individual approach is needed, including genetic and pharmacogenetic tests.